2014
DOI: 10.1215/03616878-2682630
|View full text |Cite
|
Sign up to set email alerts
|

Why FCTC Policies Have Not Been Implemented in China: Domestic Dynamics and Tobacco Governance

Abstract: The international community, under the auspices of the World Health Organization, developed the landmark Framework Convention on Tobacco Control (FCTC) to curb the global tobacco epidemic. As an internationally binding convention about global best practices on tobacco control, the FCTC has become an overriding source of policy transfer for developing countries in the fight against smoking. However, since its ratification of the first global norm over tobacco governance and against the grim background of the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…Thus the official view is one that stresses normalisation, not denormalisation, in its attitude to the tobacco industry. Consequently, although China is a party to the FCTC, the government's implementation and enforcement of tobacco control policies has been limited (Jin, 2014;Samet, 2014) and the ratio of government expenditure on tobacco control to annual tax revenue is one of the lowest globally (Lam and He, 2014). To a large extent this reflects the weakness of anti-tobacco policy networks, which remain marginalised.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus the official view is one that stresses normalisation, not denormalisation, in its attitude to the tobacco industry. Consequently, although China is a party to the FCTC, the government's implementation and enforcement of tobacco control policies has been limited (Jin, 2014;Samet, 2014) and the ratio of government expenditure on tobacco control to annual tax revenue is one of the lowest globally (Lam and He, 2014). To a large extent this reflects the weakness of anti-tobacco policy networks, which remain marginalised.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Cheng (2014) cites the Chinese Association on Tobacco Control which indicated that 52 tobacco companies donated to, or sponsored, 79 welfare activities in 40 cities and counties during the last quarter of 2009, including those, such as the Hope Project, designed to help poor children attend school (Jin, 2014), These philanthropic projects are similar to those pursued by any other tobacco company and are important in promoting a positive public image of corporate social responsibility and maintaining public support for the CNTC Yang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations